2018
DOI: 10.2147/cmar.s170818
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of aberrant <em>P16<sup>INK4a</sup></em> methylation in ovarian cancer: a meta-analysis based on literature and TCGA datasets

Abstract: Epigenetic alteration of P16INK4a is conventionally thought to induce the initiation of carcinoma. However, the role of P16INK4a methylation in ovarian cancer still remains controversial. Therefore, we performed a meta-analysis to further elucidate the relationship between P16INK4a promoter methylation and ovarian cancer. A total of 24 studies, including 20 on risk, 10 on clinicopathological features, and 3 on prognosis, were included in our meta-analysis. Our results indicated that the frequency of P16INK4a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…30 For the above reasons, hypermethylation of tumor suppressor genes can lead to poor prognosis for tumor patients. 31 In order to analyze the methylation and prognosis, we analyzed the relationship between the methylation rate of the above five sites and the prognosis of GC. The results showed that the methylation rate of M5(−148) (Chr5:64,165,959) and M27(−26)(Chr5:64,166,081) could indicate poor prognosis by setting a cut-off value of 0.3.…”
Section: Discussionmentioning
confidence: 99%
“…30 For the above reasons, hypermethylation of tumor suppressor genes can lead to poor prognosis for tumor patients. 31 In order to analyze the methylation and prognosis, we analyzed the relationship between the methylation rate of the above five sites and the prognosis of GC. The results showed that the methylation rate of M5(−148) (Chr5:64,165,959) and M27(−26)(Chr5:64,166,081) could indicate poor prognosis by setting a cut-off value of 0.3.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other authors have suggested that aberrant methylation of CDKN2A promoter may be essential to the initiation of ovarian cancer and in distinguishing malignant from healthy ovarian tissues. Besides, CDKN2A promoter methylation is a potential predictive factor for poor prognosis in ovarian cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different proteins, depending on their upregulated or downregulated status, can participate in the process of cancer development progression in addition to affecting tumor behavior and aggressiveness [10]. Thus, based on the promising biomarkers published, we selected certain targets such as: survivin and BCL2 apoptosis regulator (BCL2) that support cell division and anti-apoptotic function [11,12]; cyclin dependent kinase inhibitor 2A (CDKN2A) that regulates the progression from the G1 to the S phase in the cell cycle, the polo like kinase 1 (PLK1) that regulates the G2/M transition [13,14]; epidermal growth factor receptor (EGFR) that promotes cell survival and proliferation [15]; and nuclear cyclin D1 (CCND1) that, when accumulated, results in an aberrant increase in cell proliferation activity [16]. The main function of p63 is to maintain the proliferative potential of progenitor epidermal cells, predominantly located in basal layers.…”
Section: Introductionmentioning
confidence: 99%